'Stop Measuring Black Kids with a White Stick': Translanguaging for Classroom Assessment. (August 2022) - Steele, Carly; Dovchin, Sender; Oliver, Rhonda
In this conceptual paper, we explore the opportunities and challenges that translanguaging may provide for students from Australian Aboriginal backgrounds and their teachers. We use examples taken from Australian Aboriginal students who may speak Standard Australian English, Australian Aboriginal English, creoles (Kriol being the common one across the north of Australia) and traditional languages (e.g. Kija, Martu). We begin by examining the concept of translanguaging and show how Australian Aboriginal students can move fluidly between their various linguistic resources, dialects and repertoires to make meaning, express their thoughts, understandings and feelings, create their identities, and do so in often playful and creative ways. The principles of fair and valid assessment are explored and the role that translanguaging can fulfil for assessment purposes is considered. We also document some of the social, cultural and linguistic biases that underpin aspects of assessment, and make suggestions for improvement. In particular, we examine how teachers could approach assessment so that students with Aboriginal backgrounds are able to draw on their full linguistic repertoire and, in this way, address the issues surrounding discriminatory assessment practices that are founded on monolingual mindsets. We also take up the gauntlet to 'stop measuring black kids with a white stick' and seek positive and embracing ways for all students with Aboriginal backgrounds to engage in assessment practices.